Using acoustic telemetry to estimate post-release survival of undulate ray Raja undulata (Rajidae) in northeast Altantic. (1st August 2019) - Morfin, Marie; Simon, Julien; Morandeau, Fabien; Baulier, Loïc; Méhault, Sonia; Kopp, Dorothée
Abstract: The landing obligation introduced in the reform of the European Union Common Fisheries Policy requires landing all catches of species under quota. However, exemptions may be granted for species for which " scientific evidence demonstrates high survival rates". Captivity experiments are often used to determine fish survival rates, but they are difficult to perform for large species such as rays due to the limited storage capacity of tanks. Thus, little information is available on ray survival after release despite an identified potential for high survival. We used acoustic telemetry to study rays discarded from a coastal bottom trawl fishery in their natural environment and present a new ad hoc approach to derive a minimum survival rate. After capture under commercial conditions in a semi-enclosed bay, 144 rays were tagged with a miniature acoustic transmitter. Survival was assessed based on detections from 15 acoustic receivers deployed in the area and a mobile reception antenna. Then, combining detection data with information on currents provides useful results from a management perspective, as at least 49% of the rays were found to have survived the first 14 days after released, and because the only factor identified that likely decrease survival (i.e. smaller individuals) cannot be improved easily by changing fishing practices. Highlights: Survival rate of Raja undulata was assessed in a coastal otter trawl fishery. Rays were tracked acoustically during three months after being discarded. An ad hoc approach based on currents was developed to assess survival. At least 52% of rays survived to discarding. Fishing conditions were not detected as drivers of ray's survival.